Preliminary Study on the Effect of Nitrogen Fertilisation on Phytochemical Content Quality of Gynura procumbens - Mohamad Fhaizal, Mohamad Bukhori; Hawa Z. E., Jaafar; Ali, Ghasemzadeh; Uma Rani, Sinniah; Gayatri, Karipaya (Penerbit Universiti Sains Malaysia, 2021)
The study was carried out to examine the effects of nitrogen (N) fertilisation on phytochemical content quality, to determine types of phytochemicals compositions, and to establish phytochemicals marker compounds in Gynura procumbens. In this two factors study, three stages of harvesting (H) time and three rates of N were laid out according to Randomised Complete Block Design (RCBD). Physiological and biochemical attributes were recorded to exhibit the trend for plant quality. The results showed that, N has affected phytochemical content significantly (p < 0.05) with stronger effect on physiological and biochemical attributes (p < 0.01). The results suggested that 0 and 90 kg/ha N, respectively are highly and least effecting the Photo, Cond, TChlC, TCC, TPrc, TLiC, TPC and TFC.